PENGARUH PENILAIAN PRESTASI KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA HOTEL PANGERAN PEKANBARU - Hafizh Yusri; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of job performance appraisal and career development on employee performance partially and simultaneously. This study used a questionnaire as a data collection tool which was distributed to 65 respondents to employees of Hotel Pangeran Pekanbaru. The data was then processed using descriptive analysis and statistical analysis using SPSS 16 by performing validity tests, reliability tests, simple linear regression analysis, multiple linear regression analysis, determination analysis (R2) and hypothesis testing with t test (partial) and F test (simultaneous).The results showed that testing the first hypothesis, namely the assessment of work performance on employee performance, namely t count (3.803)> t table (1.998), meaning that job performance appraisal has an effect on employee performance. Second, career development is t count (4.194)> t table (1.998), meaning that career development has an effect on employee performance. The results of the F test (11.369)> F table (3.15) means that the simultaneous assessment of work performance and career development has an effect on employee performance.Keywords: Job Performance Assessment, Career Development, Employee Performance